Cytodiagnosis of myxoid adrenocortical carcinoma and role of immunocytochemistry to differentiate it from renal cell carcinoma - Mondal, Santosh Kumar (Medknow Publications & Media Pvt Ltd, 2014)
Adrenocortical carcinoma (ACC) is a rare malignancy and cytodiagnosis of this tumor is not routinely encountered by a cytopathologist. Here, we report a case of ACC initially diagnosed by computed tomography (CT)-guided fine needle aspiration cytology (FNAC) with the help of immunocytochemistry. A 48-year-old lady presented with flank pain and abdominal mass for the last 6 months. A CT scan of her abdomen revealed a large mass arising from the upper part of the left kidney. CT-guided FNAC was performed. Cytologic smears showed pleomorphic large cells arranged discretely and in small aggregates against a myxoid background. The cells had a high nucleocytoplasmic ratio, anisonucleosis and conspicuous nucleoli. Based on cytomorphology, differential diagnoses of ACC and renal cell carcinoma (RCC) were made. On immunocytochemistry, the tumor cells were synaptophysin, inhibin, vimentin and Melan-A positive but cytokeratin and epithelial membrane antigen negative. Thus, a cytodiagnosis of myxoid ACC was made and histopathologic examination was suggested. Subsequent histologic examination and immunohistochemistry proved the case to be myxoid ACC.